(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The rapid transformation of the educational environment in Uzbekistan has created new opportunities and challenges for small educational businesses. In recent years, private learning centers, language schools, tutoring services, and digital education platforms have become important contributors to the national education system. Growing demand for foreign language proficiency, information technologies, and professional skills has intensified competition among educational enterprises and increased the importance of strategic management and digital innovation. This study examines how small educational businesses in Uzbekistan adapt to changing market conditions through innovative approaches, digital technologies, and flexible business strategies. The purpose of the research is to analyze the mechanisms of strategic adaptation and the role of digital innovation in improving the competitiveness and sustainability of small educational enterprises. The study focuses on private educational centers operating in urban areas of Uzbekistan and evaluates their responses to economic uncertainty, technological transformation, and changing consumer expectations. Particular attention is devoted to the influence of digital platforms, social media marketing, online learning systems, and customer-oriented educational services on business development.